Comparative Analysis of Hashing Algorithms used in Data Deduplication - Selvam, J. Maria; Srivaramangai, P (International Journal of Computer Sciences and Engineering, 2025)
Now-a-days, increasing volume of digital data demands more storage space and efficient technique to handle these data. Duplicate is inevitable while handling huge amount of data. Data Deduplication is an efficient approach in storage environment that utilize different techniques to deal with duplicate data. It identifies and removes redundant data by its message digest value which is generated by using any kind of cryptographic hash algorithms such as MD5 and Secure hash algorithms. This research paper analyses the two hash algorithms, namely MD5 and SHA, based on different parameters and compare the time taken to build a hash value